Kristin Olafson-Jenkyns: The Culinary Saga of New Iceland (Recipes from the Shores of Lake Winnipeg) - Semple, Ann (Petits Propos Culinaires, 2024)
Kristin Olafson-Jenkyns: The Culinary Saga of New Iceland (Recipes from the Shores of Lake Winnipeg): Coastline Publishing, Guelph, Ontario: $32 Canada; $23.00 US.